Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound